Metrology, Inspection, and Process Control for Microlithography XXXIII 2019
DOI: 10.1117/12.2513268
|View full text |Cite
|
Sign up to set email alerts
|

Using Gaussian process regression for efficient parameter reconstruction

Abstract: Optical scatterometry is a method to measure the size and shape of periodic micro-or nanostructures on surfaces. For this purpose the geometry parameters of the structures are obtained by reproducing experimental measurement results through numerical simulations. We compare the performance of Bayesian optimization to different local minimization algorithms for this numerical optimization problem. Bayesian optimization uses Gaussianprocess regression to find promising parameter values. We examine how pre-comput… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…In a previous work [ 27 , 41 ], it was shown that the BO performs much better than other metaheuristic optimization approaches with respect to the computing time needed to find the global minimum. Since BO considers all previous function evaluations, it can be more efficient than other metaheuristic global optimization strategies [ 27 ] and local optimization strategies [ 42 ]. This is a crucial benefit here, as one model calculation takes several minutes on a standard desktop computer.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous work [ 27 , 41 ], it was shown that the BO performs much better than other metaheuristic optimization approaches with respect to the computing time needed to find the global minimum. Since BO considers all previous function evaluations, it can be more efficient than other metaheuristic global optimization strategies [ 27 ] and local optimization strategies [ 42 ]. This is a crucial benefit here, as one model calculation takes several minutes on a standard desktop computer.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous work [25,38], it was shown that the BO performs much better than other meta-heuristic optimization approaches with respect to the computing time needed to find the global minimum. Since BO considers all previous function evaluations, it can be more efficient than other meta-heuristic global optimization strategies [25] and local optimization strategies [39]. This is a crucial benefit here, as one model calculation takes several minutes on a standard desktop computer.…”
Section: Simulation and Optimization Of Fluorescence Intensitiesmentioning
confidence: 99%
“…36 Since BO takes all previous function evaluations into account it can be more efficient than other heuristic global optimization strategies 37 and local optimization strategies. 38 For example, PSO computes the next sampling position solely based on the current position and velocity of one swarm member as well as based on the best seen position of the member and the swarm.…”
Section: Simulation Of Fluorescence Intensitiesmentioning
confidence: 99%